Transição agroecológica em assentamento rural: Uma experiência dos assentados de Chico Mendes III em São Lourenço da Mata e Paudalho, Pernambuco - Chagas, Ivone Augusta Lima das (2016)
After the Second World War, the speech of increase the produtivity in order to finish the hungry consolidated and was scattered around the world from the idea of agriculture modernization based on Green Revolution. This revolution was fixed in application of technology package, a measures constituted by modified genetical varieties, using chemical inputs and large machines that depends of non-renawable energy resources. This agricultural modernization also stimulated the production through large monocultures to exportation, that cames with many social and environment negative impacts. These associated with concentration lands contributed for that this model was considered, by many authros, as "conservative modernization". In this context, comes up the Agroecology as an alternative to this degrading and exclusionary model implamentation. However, still exists many challenges to consolidate a new developmental model. Against this problematic, this study had as objective analyse the process of agroecological transition experienced in a settlement called Chico Mendes III. The research came from the hypothesis that agroecological transition in rural settlements provides the increase of local social environments conditions, but this process cames with many difficulties and challanges. To understand this reality, this study was based on dialectic approach and as methodological process, was used bibliographic reaseach, local visits, qualitative analysis from 20 interviews made with different actors involved in this process. The research results show many agroecological experiences, as the perception of settlers about agroecology, but also, indicated many obstacle and challange faced by settlers in transition process. Concludes that the curse of agroecological transition in the settlement provides the increase of local social environment conditions, but this transition process needs more family involvement and public policy that enable and strengthen this way in rural settlements.